Loosing Your Head for Artemisia - Zappelli Cerri, Gabrio (2015)
In different artistic languages such as painting, there is a use of the kinetic potential, but the movement remains virtual. In the present paper investigates this “time of content” in some paintings chosen by Artemisia Gentileschi (Judith and Holofernes), who rely on a “dramatic script” of sequences designed for painting, she took the theme of decapitation, which allowed in 1960 the European feminist movement and celebrate the discovery of a martyr and hero of his time. By observing the sequences a “little horror story” is reconstructed, which is told through different pictorial representations of the same dramatic story and it allows locating the following three stages: the decapitation, the flight and the triumph through the frame and sequence. Therefore, in this content, frame and sequences analysis delimit the movement to be considered such a syntactic component as the semantic content of kinetic rate on an image in time. The kinetics of Artemisia produces pictorial narrative motion pictures, which goes beyond a simple recording of the “film” virtual sequences frozen on the canvas.